Extradosed Bridges in Poland—Design and Construction - Biliszczuk, Jan; Onysyk, Jerzy; Barcik, Wojciech; Toczkiewicz, Robert; Tukendorf, Artur (Frontiers in Built Environment, 2017)
The road and railway infrastructure in Poland has been intensively developed and modernized for the last years. Around 300 new bridges are built annually. Among the new structures, there is a group of modern extradosed bridges. This paper presents examples of short-, medium-, and long-span extradosed bridges designed and built in recent years in Poland. The following structures are described in details: (1) the first Polish extradosed bridge; (2) two-span landmark viaduct over motorway; (3) multi-span curved motorway bridge; (4) the longest Polish extradosed bridge; (5) tramway extradosed bridge; and (6) conceptual designs. The paper is concluded with geometrical parameters characterizing presented structures. The parameters are compared with values obtained for cable-stayed bridges and extradosed bridges built worldwide.